PERBANDINGAN SISTEM HUKUM TENTANG REGULASI KEJAHATAN TANPA KORBAN DI KAWASAN ASIA - Duwi Handoko; Beni Sukri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Victimless crime is an important thing to know, both in terms of aspects related to crime patterns and imposition of sanctions against violator. The reason is that it is not appropriate to punish someone who does not harm others.In a discussion that the author does, it is not appropriate if someone is punished for having the potential to become a